Gender Differences in the Relationship between Strain, Negative Emotions and Delinquent Behaviors in Institutionalized Juveniles. Issue 9 (1st September 2020) - Habersaat, Stéphanie; Boonmann, Cyril; Schmeck, Klaus; Stéphan, Philippe; Francescotti, Eric; Fegert, Jörg M.; Perler, Christian; Schmid, Marc; Urben, Sébastien
ABSTRACT: The aim of the current study was to examine the influence of strain, anger-irritability problems and depressed-anxious symptoms on delinquent behavior problems as well as the moderating effect of depressed-anxious symptoms on the relationship between anger-irritability problems and delinquent behaviors in a sample of 248 institutionalized boys and 128 girls. Results showed that both strain and anger-irritability problems were independently related to delinquent behavior problems in boys and in girls. Depressed-anxious symptoms were related to delinquent behavior problems in girls only, and they did not moderate the relationship between anger anxiety problems and delinquent behavior problems. The model explained two times more variance (42% in girls; 19% in boys) of the delinquent behavior problems in girls than in boys, thus suggesting that a higher level of negative emotions seem to play a larger part in girls' offending behavior than in boys'.